Purification and In situ Iodisation of Blotong Solid Waste into Consumption Salt in Iodized-Salt Industry - Nilawati Nilawati; Marihati Marihati (Biopropal Industri, 2015)
The solid waste of iodized-salt industry are sapon (50-100 kilograms) and blotong (1-2 tons) per 10 tons per day. The objective of this research was for recycling blotong through purification, recrystallization and in situ iodisation to increase NaCl content and homogeneous KIO3. This research used two variables which were KIO3 concentration within 30,40, 50 & 60 ppm, and brine water of blotong that had soluted into 240Be (consist of salt water which purified with Na2CO3, NaOH and unpurified salt water). The composition of blotong were 12.318% water content, 46.409% Cl-, 82.685% pure NaCl, 0.784% Mg2+, 1.420% Ca2+ and 2.747% SO4.After purification and recrystallization, impurities was decreased, Mg2+ became 0.278% (64.54% reduction) and Ca2+ became 0.153% (89.23% reduction). NaCl content was increasing into 96.481% and fulfilled the NaCl standard of salt consumption based on SNI 3556-2010 (94.7%).